2020
DOI: 10.3390/ijms21103667
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilin A Promotes Inflammation in Acute Kidney Injury but Not in Renal Fibrosis

Abstract: Cyclophilin A (CypA) is a highly abundant protein in the cytoplasm of most mammalian cells. Beyond its homeostatic role in protein folding, CypA is a Damage-Associated Molecular Pattern which can promote inflammation during tissue injury. However, the role of CypA in kidney disease is largely unknown. This study investigates the contribution of CypA in two different types of kidney injury: acute tubular necrosis and progressive interstitial fibrosis. CypA (Ppia) gene deficient and wild type (WT) littermate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 46 publications
(68 reference statements)
0
17
0
Order By: Relevance
“…CypA−/− mice were protected against loss of renal function and tubular cell death in a 24 h model of renal IRI model. This protection was attributed to the profound reduction in neutrophil infiltration in CypA−/− mice, given that CypA−/− tubular cells are not protected from reactive oxygen species-induced cell death [ 36 ]. Thus, the dramatic protection seen against the loss of renal function with GS-642362 treatment in severe renal IRI may be due to the additive benefits of blockade of both CypD-mediated tubular necrosis and inhibition of CypA-dependent neutrophil-mediated tubular cell death and damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CypA−/− mice were protected against loss of renal function and tubular cell death in a 24 h model of renal IRI model. This protection was attributed to the profound reduction in neutrophil infiltration in CypA−/− mice, given that CypA−/− tubular cells are not protected from reactive oxygen species-induced cell death [ 36 ]. Thus, the dramatic protection seen against the loss of renal function with GS-642362 treatment in severe renal IRI may be due to the additive benefits of blockade of both CypD-mediated tubular necrosis and inhibition of CypA-dependent neutrophil-mediated tubular cell death and damage.…”
Section: Discussionmentioning
confidence: 99%
“…While CypA−/− mice are protected from renal IRI, they do not show protection in the day 7 UUO model in terms of tubular damage, macrophage infiltration, interstitial collagen IV deposition, or upregulation of kidney collagen I or α-SMA mRNA levels [ 36 ]. However, we cannot rule out a potential added benefit of blockade of both CypA and CypD using GS-642362 in the UUO model.…”
Section: Discussionmentioning
confidence: 99%
“…Rats underwent bilateral IRI, as previously described. 14,15 Male rats were anesthetized with ketamine and xylazine. A heating blanket connected to a rectal thermometer was used to maintain body temperature at 37 C. Following a midline abdominal incision, both renal pedicles were clamped using non-traumatic vascular clamps for 25 minutes, during which the abdomen was temporarily sutured.…”
Section: Bilateral Irimentioning
confidence: 99%
“…In this current Special Edition, thirteen original research articles are presented: twelve in vivo studies in a murine or rat model and one in vitro study [ 3 ]. Seven studies show results from AKI models [ 4 , 5 , 6 , 7 , 8 , 9 , 10 ], five from fibrosis models (or CKD models) [ 9 , 11 , 12 , 13 , 14 ] and two from a transplant rejection model [ 4 , 15 ] (two studies used two different in vivo models).…”
mentioning
confidence: 99%
“…Leong and coworkers showed that cyclophilin A, a damage-associated molecular pattern, promoted inflammation and acute kidney injury in a renal IR model but did not contribute to inflammation or interstitial fibrosis in a model of progressive kidney fibrosis (unilateral ureteric obstruction (UUO)) [ 9 ]. Other studies showed the effects of different proteins/peptides against UUO-induced renal injury, inflammation and fibrosis.…”
mentioning
confidence: 99%